Isotretinoin has no negative effect on attention, executive function and mood - ÖZAYDIN, AYŞE NİLÜFER; ERGUN, SAFİYE ATLAS TÜLİN; ZAİMOĞLU, SENNUR (WILEY, 2012)
Background According to some animal data, impairments in learning and memory are seen with isotretinoin. Isotretinoin has been shown to affect human brain metabolism, but the data on human neural functions is lacking. Objectives To evaluate whether isotretinoin treatment affects cognitive functions, causes depression and anxiety or alters anger level and anger expression. Methods Neuropsychological tests of attention and executive functions, behavioural tests measuring anger and depression and measures assessing acne severity were applied to 63 severe and / or resistant acne patients from four medical centres including one primary care institute and three university hospitals at the beginning, at the end of first month, third month and at end of treatment with isotretinoin. Results From a total of 63 patients, 15 missed the final visit and 48 were evaluated. Overall, 11 (six women, five men) and five (all women) patients reported anger and depression, respectively, during treatment. Eleven of these 16 patients improved spontaneously. No detrimental effects of isotretinoin treatment on either executive functions or mood were found. Several executive functions and control of anger trait were found to be improved. Clearing of acne was obtained in 94.6% of patients. Limitations Improvement of several measures may be related to learning effect of repeated testing. Investigating brain functions is a complex process and various methods can be used. Conclusion The test battery used in this study, which is commonly used to evaluate mental status both in adults and children, did not show any negative effect of isotretinoin on executive functional parameters in acne patients.
Keywords: 13-CIS-RETINOIC ACID ALTERS; RETINOIC ACID; ACNE PATIENTS; DISABILITY INDEX; DEPRESSION; MEMORY; RATS; MICE; BEHAVIOR; RECEPTOR